Defining pharmacists' roles in disasters: A Delphi study - Watson, Kaitlyn E. (PLoS One, 2019)
INTRODUCTION: Pharmacists are uniquely placed in the community to be of assistance to disaster-affected patients. However, the roles undertaken by pharmacists in disasters are identified based on their own experiences and networks. There is currently no definition or acknowledgment of pharmacists’ roles in disasters. OBJECTIVE: To acquire consensus from an expert panel of key opinion leaders within the field of disaster health on pharmacists’ roles in disasters throughout the four disaster phases—prevention, preparedness, response, and recovery. METHODS: A Delphi study consisting of three rounds of online surveys was utilised. Twenty-four key opinion leaders were contacted, with 15 completing all three rounds. The 15 expert panellists were presented with 46 roles identified in the literature and asked to rank their opinions on a 5-point Likert scale. This study used an international, all-hazard, and multijurisdictional approach. Consensus was benchmarked at 80% and any role which did not reach consensus was re-queried in the subsequent round. The third round provided the results of the Delphi study and sought commentary on the acceptance or rejection of the roles. RESULTS: Of the 46 roles provided to the expert panel, 43 roles were accepted as roles pharmacists are capable of undertaking in a disaster. There were five roles for the prevention phase, nine for the preparedness phase, 21 for the response phase, and eight for the recovery phase. The experts were asked to prioritise the top five roles for each of the disaster phases. The three roles which did not make consensus were deemed to be specialised roles for disaster pharmacists and not generalisable to the broader pharmacy profession. CONCLUSION: This study identifies pharmacists’ roles in disasters which have been accepted by the international disaster health community. The international key opinion leaders recommended that pharmacists could be undertaking 43 roles in a disaster, however, this is dependent on individual jurisdiction considerations. Pharmacy professional associations need to advocate to policymakers for legislative support and to ensure pharmacists are equipped with the training and education required to undertake these roles within specific jurisdictions.